CEO age and gender: Subsequent market performance - Marcelo Eduardo (Taylor & Francis Group, 2016)
The issue of CEO age and gender vs. concurrent performance is extensively examined, but the association with subsequent performance has limited treatment in the financial literature, and with conflicting findings. In the current study, we examine the association between CEO age and gender, and subsequent company market performance using a more recent set of observations and the standard four-factor model to estimate future cumulative abnormal shareholder returns. We find that subsequent abnormal shareholder returns are marginally significantly higher for female CEOs than for their male counterparts, but no material pattern is observed between CEO age and subsequent abnormal shareholder return performance.